HAMBATAN SISTEM, DUKUNGAN MANAJEMEN, DAN BUDAYA KESELAMATAN DALAM PELAPORAN DAN INVESTIGASI KECELAKAAN DAN PENYAKIT AKIBAT KERJA DI RUMAH SAKIT - Yulyanti, Depi; Fadil Ahmad Junaedi; Tony Prabowo; Fauzi Nurrahman Hidayat; Helma Halimarussadiyah (Journal of Hospital Administration and Management (JHAM), 2025)
Occupational safety and health is an important issue in hospitals due to the high number of accidents and occupational diseases that can occur among both healthcare and non-healthcare workers. Incident reporting and investigation are important aspects of achieving continuous learning and incident prevention, but in practice, each still faces several challenges. This study aims to examine the experiences of hospital staff with reporting and investigating work-related injuries and illnesses from the perspectives of systemic barriers, management support, and safety culture. This study uses an exploratory qualitative approach and was conducted in six hospitals in the Tasikmalaya region, including government and private hospitals. Data collection was carried out through in-depth interviews, observations, and triangulation of other data with informants from the management team, the K3RS team, unit heads, and employees who had experienced KAK or PAK. The data were analyzed using thematic analysis. The results show that staff awareness and motivation to report incidents already exist, although less serious cases are not routinely reported, while serious cases are automatically reported because they are related to BPJS Ketenagakerjaan claims. Limitations in the reporting process are due to the system still being manual, as there is no digital reporting system in place, complex administration, and a shortage of human resources in the K3RS department, particularly occupational specialists or doctors who have undergone Hiperkes and Occupational Health training. Management support is quite responsive, but the safety culture that has developed is still reactive. Therefore, the study found that although reporting and health transparency in hospitals can still be implemented, strengthening the system, management, and a responsive safety culture is necessary to ensure that incident prevention can occur sustainably.